2021
DOI: 10.3390/cells10113065
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Pathway Inhibition with NVP-BEZ235 Hinders Glycolytic Metabolism in Glioblastoma Multiforme Cells

Abstract: Glioblastoma (GBM) is the most lethal primary brain cancer that lacks effective molecular targeted therapies. The PI3K/AKT/mTOR pathway is activated in 90% of all Glioblastoma multiforme (GBM) tumors. To gain insight into the impact of the PI3K pathway on GBM metabolism, we treated U87MG GBM cells with NVP-BEZ235 (PI3K and mTOR a dual inhibitor) and identified differentially expressed genes with RNA-seq analysis. RNA-seq identified 7803 differentially regulated genes in response to NVP-BEZ235. Gene Set Enrichm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Shreya et al found that inhibiting PI3K-mTOR resulted in decreased levels of glycolytic metabolites, including a significant reduction in NAD+ and glutamate metabolites in GBM. Moreover, decreased glucose uptake and lactate secretion were also observed in this study [72] .…”
Section: Signaling Network Of Metabolic Reprogrammingsupporting
confidence: 79%
“…Shreya et al found that inhibiting PI3K-mTOR resulted in decreased levels of glycolytic metabolites, including a significant reduction in NAD+ and glutamate metabolites in GBM. Moreover, decreased glucose uptake and lactate secretion were also observed in this study [72] .…”
Section: Signaling Network Of Metabolic Reprogrammingsupporting
confidence: 79%
“…In GBM cells, upon either FOXO1 or PI3K/mTOR inhibition, the expression of genes involved in glycolysis, such as LDHA, is reduced. However, surprisingly when both of them are inhibited, not only LDHA but ENO1 as glycolytic genes associated with poorer survival are increased, supporting the theory that for the efficacy of PI3/mTOR inhibitors against glycolysis, the intact activity of FOXO1 is necessary [ 143 ](Fig. 5 B).…”
Section: Foxo Familymentioning
confidence: 63%
“…In addition, PI3K/mTOR or FOXO1 inhibitors could prevent glycolysis in gliomas. However, when both of them are concurrently inhibited, the expression of glycolysis-related genes, including LDHA and ENO1, is elevated [ 143 ].…”
Section: Foxo Familymentioning
confidence: 99%
“…EGFR signaling also induces the downstream activation of HIF-1 and PI3K/AKT/mTOR signaling, which rewires glycolysis and the PPP [ 47 ]. The PI3K/AKT/mTOR pathway not only increased glycolysis by elevating the expression of glucose transporters and the glycolytic rate but also decoupled glycolysis and the TCA cycle and diverted metabolic intermediates to the PPP branching metabolic pathway [ 48 , 49 ]. The increased flux in glycolysis and the PPP provided survival benefits to cancer cells after radiation.…”
Section: Discussionmentioning
confidence: 99%